2014
DOI: 10.3923/pjbs.2014.667.674
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid (Meleagrine and Chrysogine) from Endophytic Fungi (Penicillium sp.) of Annona squamosa L.

Abstract: Several endophytic fungal strains from Srikaya plants (Annona squamosa L.) have been isolated and one of them was identified as Penicillium sp. Penicillium has been proven as an established source for a wide array of unique bioactive secondary metabolites that exhibit a variety of biological activities. The aim of this study is isolation of secondary metabolite from Penicillium, an endophytic of A. squamosa L. Penicillium sp. from endophytic of A. squamosa L. was fermented in Wicherham media. The whole extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This may support the observation that why a species of endophyte can synthesise a bioactive compound in one plant but is unable to do so when isolated from another host species . This fact is supported by various investigations on many endophytic species like Fusarium , Colletotrichum , Alternaria , Aspergillus , Emericella , Penicillium , Pestalotiopsis , Xylaria , Bacillus , Streptomyces , and some others . In these studies, researchers have reported different important molecules from the same endophyte while isolating it from host plants of different ecoregions.…”
Section: Chemoprofile Diversity Of Endophytessupporting
confidence: 60%
“…This may support the observation that why a species of endophyte can synthesise a bioactive compound in one plant but is unable to do so when isolated from another host species . This fact is supported by various investigations on many endophytic species like Fusarium , Colletotrichum , Alternaria , Aspergillus , Emericella , Penicillium , Pestalotiopsis , Xylaria , Bacillus , Streptomyces , and some others . In these studies, researchers have reported different important molecules from the same endophyte while isolating it from host plants of different ecoregions.…”
Section: Chemoprofile Diversity Of Endophytessupporting
confidence: 60%
“… 18,19 These compounds are commonly produced in extracts of fungi of the genus Penicillium 20,21 . Meleagrin has already been isolated from fungi of the genus Penicillium isolated from A. squamosa 22 ; however, this metabolite can be isolated from fungi of different environments 21,23 and is not exclusive to endophytic fungi of Annona , which suggests that it is a metabolite that is related to the phylogeny of the group.…”
Section: Resultsmentioning
confidence: 99%
“…MS/MS data associated with each metabolite within each extract were referenced against the ones available in databases (MarinLit, Dictionary of Natural Products, Scifinder and Chemspider) and the published data (Uchida et al 1996;Kusano et al 1997;Komai et al 2005;Liu, Sutton and Sternglanz 2005;Du et al 2010;Yunianto et al 2014;Dekan et al 2019;Wang et al 2019a). The main compound produced by Penicillium sp.…”
Section: Antibacterial Screening Resultsmentioning
confidence: 99%
“…Thus, this is the first time that these compounds have been identified from fungi isolated from the marine environment. Concerning the biological activities of the annotated compounds, the compound meleagrin does not exhibit antimicrobial activities with the disk diffusion method (Yunianto et al 2014). The antibiofilm activity of meleagrin was investigated against Gram-positive (S. aureus ATCC 29213) and Gram-negative (P. aeruginosa ATCC 9027) bacteria, and found to have a minimum inhibitory concentration (MIC) of 0.25 mg/mL and 0.6 mg/mL, respectively (Hamed et al 2020).…”
Section: Secondary Metabolitesmentioning
confidence: 99%